A vision-based intelligent transportation system for high tech cities - Mohamad Syahrul Syafiq Mohamad Nasir (Nanyang Technological University, 2020)
While it has become common practice to utilize image processing algorithms to help modernize road traffic regulation, there are still many issues within the system that must be addressed. This project focuses on the usage of theoretical image processing algorithms in an object- orientated development environment and its real-world applications. This includes using MATLAB as a way of simulating a local, vision-based system that can be adopted for use in traffic monitoring systems. This project will be covering the entire program development which includes structure modelling, source coding, GUI rendering, data binding and development-side testing. The project then applies the result to develop several different applications through the compilation of MATLAB. These include: consolidating the primary image processing algorithms into a generic image parser and recognizing vehicle registration plate thereby segmenting characters using OCR. Furthermore, this project investigates the feasibility of using vision-based processing algorithms in video surveillance systems to better manage road traffic. Finally, the thesis presents the experimental findings that have been discovered throughout the project and lays out the methodologies of image processing that can be applied to road traffic management.